ANALISIS RESEPSI AUDIENS TERHADAP NILAI KELUARGA DALAM FILM HOME SWEET LOAN - Tiara Shafa Salsabila; Genny Gustina Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Films not only function as a form of entertainment but also as a medium of representation that builds meaning about social reality, including family values. The film Home Sweet Loan represents the dynamics of Indonesian families through economic conflicts, responsibilities among family members, individual sacrifices, and complex family relationships. This study aims to analyze how audiences interpret the representation of family values in the film Home Sweet Loan based on Stuart Hall's reception analysis perspective. The research uses a qualitative approach with a reception analysis method. Data were collected through Focus Group Discussions (FGD) involving 23 participants and in-depth interviews with eight informants selected using purposive sampling techniques. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions according to Miles and Huberman, while data validity was tested using source triangulation and method triangulation. The research results show that audiences understand family as a space of moral responsibility, a space of devotion as well as individual burden, and a relationship built through support, conflict, and role division. Based on Stuart Hall's encoding-decoding theory, three reception positions were found: dominant-hegemonic position, negotiated position, and oppositional position. The negotiated position is the most dominant because the audience still acknowledges the importance of family solidarity, but begins to negotiate the limits of individual sacrifice according to their social experiences. Audience interpretation is influenced by social background, life experiences, and the cultural values each individual holds, so the meaning produced regarding family representation in film is diverse and dynamic. Keywords: Reception Analysis; Stuart Hall; Family Values; Home Sweet Loan; Encoding Decoding